Maximum topological distance-based indices as molecular descriptors for QSPR 3 : Calculation of the hydrophobicity of polyaromatic hydrocarbons - Tueros, Matías Jorge (2001)
Maximum topological distance-based indices are used together with standard ones to compute the hydrophobicity of polyaromatic hydrocarbons. Several variables and higher-order regression equations are computed and shown to be excellent predictors for the chosen physical-chemistry property. This new alternative offers advantages the usual manner of deriving global topological indices for QSPR. Some possible future extensions are pointed out.